The Historic Gold Mining in the High Terva River Basin (Northern Portugal) - Alexandre Lima (2014)
The Rio Terva drainage basin is known for many different Roman Gold Mine vestiges that can be found in the bibliography. This work is about research done in the region, principally in geochemistry anomalies and their relationship with the mining exploitations. The recent exploration campaigns in the area were able to identify in deep a gold mineralization, punctually very rich (50 g/t). There are also coarse gold as small nuggets of almost half millimetre. All these data were integrated in a Geographic Information System (GIS) project, in order to clarify some doubts from the field work, principally in relation with the identification of real ancient gold mines instead of exploration works or another kind of structures.